Tay-Sachs Disease: Two Novel Rare HEXA Mutations from Pakistan and Morocco - Bibi, Farah; Ullah, Asmat; Bourinaris, Thomas; Efthymiou, Stephanie; Kriouile, Yamna; Sultan, Tipu; Haider, Shahzad; Salpietro, Vincenzo; Houlden, Henry; Kaukab Raja, Ghazala (Klinische Pädiatrie, 2021)
Background Tay-Sachs disease (TSD) is a rare autosomalrecessive genetic disorder characterized by progressive destruction of nerve cells in the brain and spinal cord. It is caused by genetic variations in the HEXA gene leading to a deficiency of β hexosaminidase A (HEXA) isoenzyme activity. This study aimed to identify causative gene variants in 3 unrelated consanguineous families presented with TSD from Pakistan and Morocco.Methods Detailed clinical investigations were carried out on probands in 3 unrelated consanguineous families of Pakistani and Moroccan origin. Targeted gene sequencing and Whole Exome Sequencing (WES) were performed for variant identification. Candidate variants were checked for co-segregation with the phenotype using Sanger sequencing. Public databases including ExAC, GnomAD, dbSNP and the 1,000 Genome Project were searched to determine frequencies of the alleles. Conservation of the missense variants was ensured by aligning orthologous protein sequences from diverse vertebrate species.Results We report on 3 children presented with Tay-Sachs Disease. The β hexosaminidaseA enzyme activity was reduced in the Pakistani patient in one of the pedigrees. Genetic testing revealed 2 novel homozygous variants (p.Asp386Alafs*13 and p.Trp266Gly) in the gene HEXA in Pakistani and Moroccan patients respectively.The third family of Pakistani origin revealed a previously reported variant (p.Tyr427Ilefs*5) in HEXA. p.Tyr427Ilefs*5 is the most commonly occurring pathogenic variationin Ashkenazi but was not reported in Pakistani population.Conclusion Our study further expands the ethnic and mutational spectrum of Tay-Sachs disease emphasizing the usefulness of WES as a powerful diagnostic tool where enzymatic activity is not performed for Tay-Sachs disease. The study recommends targeted screening for these mutations (p.Tyr427Ilefs5) for cost effective testing of TSD patients. Further, the study would assist in carrier testing and prenatal diagnosis of the affected families.
Keywords: β -hexosaminidase A; GM2 gangliosidosis; Tay-Sachs disease; lysosomal storage disorder